1998
DOI: 10.1183/09031936.98.11061263
|View full text |Cite
|
Sign up to set email alerts
|

Specific immunotherapy downregulates peripheral blood CD4 and CD8 T-lymphocyte activation in grass pollen-sensitive asthma

Abstract: Several lines of evidence indicate that specific immunotherapy may act by modifying the immune responses of T-lymphocytes to the antigen. To evaluate the effect of specific immunotherapy on the activation of T-lymphocytes by cluster of differentiation cells (CD4+ and CD8+) in peripheral blood, the expression of two surface activation markers, the p55 interleukin-2 receptor (CD25) and human leucocyte antigen (HLA)-DR, was studied prospectively on circulating CD4+ and CD8+ T-cell subsets in subjects with grass-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Although in our previous study [29 ] we showed a downregulation of T‐cell activation in peripheral blood from asthmatic subjects after 1 year's IT for grass pollen‐sensitive asthma, in the present study we were unable to show any significant difference in the expression of CD25 and HLA‐DR in either peripheral blood CD4 + or CD8 + T cells during the study. This discrepancy may be due to the fact that in the previous study we examined subjects with grass pollen‐sensitive asthma out of the pollen season, whereas at present we examined asthmatic patients undergoing continuos exposure to the sensitizing antigen.…”
Section: Discussioncontrasting
confidence: 91%
“…Although in our previous study [29 ] we showed a downregulation of T‐cell activation in peripheral blood from asthmatic subjects after 1 year's IT for grass pollen‐sensitive asthma, in the present study we were unable to show any significant difference in the expression of CD25 and HLA‐DR in either peripheral blood CD4 + or CD8 + T cells during the study. This discrepancy may be due to the fact that in the previous study we examined subjects with grass pollen‐sensitive asthma out of the pollen season, whereas at present we examined asthmatic patients undergoing continuos exposure to the sensitizing antigen.…”
Section: Discussioncontrasting
confidence: 91%
“…CD25 on T lymphocytes and CD23 on B lymphocytes, in induced sputum of stable mild asthmatics. On the other hand, Majori et al[ 17] found decreased CD25 expression on T cells and decreased CD23 expression on B cells in asthmatic patients sensitized to pollen 1 year after immunotherapy in comparison to healthy controls. The aim of the present study was to determine whether food challenge in children with asthma and food allergy changes the number and activity of immune system cells involved in the inflammatory process underlying these diseases, via the determination of CD25 (IL-2R) antigen expression on T lymphocytes and CD23 (FcεRII) antigen expression on B lymphocytes before and after food challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have shown that there is a relative reduction in tissue mast cells and eosinophils associated with immunotherapy [5–13]. Changes in cytokine production by CD4 + and CD8 + T cells are now well documented and although there are differences between study systems, these changes may include: reduction in T‐helper type 2 (Th2) cytokines; elevation in Th1 cytokines; and elevation in IL‐10, regulatory T cells and/or transient anergy [5, 14–46]. Overall these data are consistent with a central role for changes in T cell function for acquisition of clinical tolerance to allergens.…”
Section: Introductionmentioning
confidence: 62%